(untitled) (Journal of Research Updates in Polymer Science, 2024)
With many existing contagious diseases, SARS-CoV-2 exemplifies the dangers of emerging infectious diseases, potentially leading to severe acute respiratory syndrome (SARS). In March 2020, the World Health Organization (WHO) declared COVID-19 a pandemic in response to the rapid increase in infections globally. This situation not only highlighted the vulnerability of populations to dangerous pathogens but also underscored the persistent challenges faced by the public health community in preventing and controlling contagious diseases. Furthermore, it led to excessive use of plastics that harm the environment, such as 70% alcohol due to its low cost and ease of use, which increased the use of plastic packaging and its improper disposal. There are studies on bioplastics reinforced with plant fibers, showing good mechanical properties, and using polymer nanocomposites with metal oxide nanoparticles, such as copper, where their incorporation can achieve optical, electronic, mechanical, and antimicrobial enhancements through the filament extrusion process. Therefore, the matrix is not only a support for the nanoparticles but can also improve antibacterial performance and expand the applications of this material to meet different requirements. The objective of this study is to produce, through extrusion, antimicrobial bioplastic filaments (PLA, plant fiber, and copper nanoparticles) for use in 3D printing and evaluate their tensile mechanical properties, Optical Morphology (OM), and Scanning Electron Morphology (SEM). The filaments produced with a plant fiber particle size of 140 µm exhibited superior quality and better mechanical performance, with tensile strengths of 33.63 and 23.83 MPa and elastic moduli of 2.69 and 5.45 GPa compared to those with a particle size of 30 µm.